Reconfigurable Computing: Architectures, Tools and Applications 7th International Symposium, ARC 2011, Belfast, UK, March 23-25, 2011, Proceedings - Koch, Andreas.; Koch, Andreas.; Krishnamurthy, Ram.; Krishnamurthy, Ram.; McAllister, John.; McAllister, John.; Woods, Roger.; Woods, Roger.; El-Ghazawi, Tarek.; El-Ghazawi, Tarek. (Theoretical Computer Science and General Issues, 2011)
This book constitutes the refereed proceedings of the 7th International Symposium on Reconfigurable Computing: Architectures, Tools and Applications, ARC 2011, held in Belfast, UK, in March 2011. The 40 revised papers presented, consisting of 24 full papers, 14 poster papers, and the abstracts of 2 plenary talks, were carefully reviewed and selected from 88 submissions. The topics covered are reconfigurable accelerators, design tools, reconfigurable processors, applications, device architecture, methodology and simulation, and system architecture.